2006
DOI: 10.1108/13664380680001078
|View full text |Cite
|
Sign up to set email alerts
|

A model for contractors’ selection in Nigeria

Abstract: Construction projects in Nigeria are generally characterized by cost and time overrun, substandard work, disputes and abandonment; emanating from several factors of which the wrong choice of contractors is a key factor. This study evaluated the criteria adopted by clients and consultants in contractors’ selection in Nigeria. Data were collected with the aid of questionnaire administered on clients and consultants within the Nigerian construction industry. Also prequalification/bid evaluation scores for eighty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The past literature reveals that there are three types of tender that are practiced in Europe [1], Malaysia, and Nigeria [2]. These are:…”
Section: Literature Review On Contractor Selectionmentioning
confidence: 99%
“…The past literature reveals that there are three types of tender that are practiced in Europe [1], Malaysia, and Nigeria [2]. These are:…”
Section: Literature Review On Contractor Selectionmentioning
confidence: 99%
“…Contract awards are tainted with elements of bribery and corruption. This lack of transparency tends to create an atmosphere for alienation of the enduser in the contract awarding process, and consequently affects user elements of contract execution efficiency (Ogunsemi and Aje, 2006).…”
Section: Figure 1 End-user Participation Modelmentioning
confidence: 99%
“…Evidently, contractor to handle the delivery of construction project normally pass through screening and selected based on a number of selection criteria [7 -9]. The criteria usually adopted include past performance, business location, technical capability, financial soundness, resources, quality assurance among others [8]; [10] and [9]. The study carried out by [11] indicated that civil engineering project involve dealing with nature, large-scale construction activities, complex structures and takes longer time to achieve.…”
Section: Introductionmentioning
confidence: 99%